Pengelolaan Sampah Plastik dengan Metode Ecobrick sebagai Upaya Mendukung SDGs ke-12: Konsumsi dan Produksi yang Bertanggung Jawab - Rahmatullah, Sri; Verawati, Ni Nyoman Sri Putu (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Abstract: Ecobricks can be a way to overcome the problem of environmental pollution by reducing plastic waste and using it into useful furniture. Through the KKN PMD (Village Community Empowerment) service activity organized by Mataram University students with the aim of inviting elementary school students to utilize and process waste into useful new products. This activity was carried out on July 8 2024 at 09.00-12.00 WITA which was held at SDN SUBAHNALA, Peresak Village, Batukliang District, Central Lombok. The method we apply in this community service is to convey the material orally and condense the making of ecobricks. It is hoped that this activity can educate students and thus increase their participation in managing sustainable waste. The implementation of this activity received a positive response from enthusiastic students who had the potential to reduce the amount of waste produced from students' consumption activities. The result of this KKN service activity is to increase students' awareness about the importance of maintaining environmental cleanliness, how to manage plastic waste, so that students have broader knowledge about environmental conservation efforts through the use of ecobricks in construction. Ecobricks can be used as furniture for various purposes, such as tables and chairs.